2001
DOI: 10.1080/14622200110043095
|View full text |Cite
|
Sign up to set email alerts
|

Cotinine binding to nicotinic acetylcholine receptors in bovine chromaffin cell and rat brain membranes

Abstract: Cotinine is the major metabolite of nicotine. It has nicotine-like biological activity, but its potency is low. We studied cotinine binding to nicotinic receptors labelled with [3H]epibatidine. In membranes from cultured bovine chromaffin cells [3H]epibatidine bound to two apparent sites with K(d) values of 93 and 1400 pM. The low-affinity binding represented two-thirds of the binding sites. In rat frontal cortex and hippocampus homogenate membranes, only one apparent binding site was detected. The Kd values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Moreover, in rats and mice, α 7 -nAChR activation enhances field stimulation-evoked glutamate currents [43, 44, 47, 48]. However, cotinine is also a low affinity ligand at heteromeric nAChRs including those composed of α3/α6β2 and α4β2-nAChR subunits [11, 12, 13, 18]. Importantly, selective ligands at α4β2-nAChRs (e.g., Sazetidine-A) have also been shown to attenuate impairments in tasks of sustained attention associated with MK-801 [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in rats and mice, α 7 -nAChR activation enhances field stimulation-evoked glutamate currents [43, 44, 47, 48]. However, cotinine is also a low affinity ligand at heteromeric nAChRs including those composed of α3/α6β2 and α4β2-nAChR subunits [11, 12, 13, 18]. Importantly, selective ligands at α4β2-nAChRs (e.g., Sazetidine-A) have also been shown to attenuate impairments in tasks of sustained attention associated with MK-801 [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cotinine was found to have very low potency in producing cardiovascular or respiratory effects [7], in altering electroencephalogram activation, or producing behavioral arousal [8], and it did not generalize to the discriminative stimulus properties of nicotine [9]. In nicotinic acetylcholine receptor (nAChR) binding assays, cotinine was also found to be approximately 100–1000 fold less potent than nicotine at displacing radiolabeled nAChR ligands in rodent brain preparations [1013]. Moreover, in functional assays, cotinine was approximately 30–50 fold less potent than nicotine in evoking dopamine release in brain slices or synaptosomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the neuroprotective effects of nicotine and acetylcholinesterase inhibitors (AChEIs) observed previously in Aβ 1–42 and glutamate neurotoxicity models is related to direct (nicotine) and indirect (AChEIs) effects at α 4 β 2 and α 7 nicotinic acetylcholine receptors (nAChRs) as well as effects on the PI3K-Akt pathway, activation of calcineurin, and L-type calcium channels. 2730 In older nAChR binding assays, cotinine was found to be approximately 100–1000 fold less potent than nicotine at displacing radiolabeled nAChR ligands 3134 , therefore, it appears unlikely that the neuroprotective effects of cotinine observed in the Aβ 1–42 neurotoxicity assay (i.e., at similar concentrations to nicotine) could be fully explained by direct effects at nAChRs. Interestingly, effectiveness of nicotine and cotinine and some other compounds (e.g., choline analogs) in memory-related behavioral tasks has been correlated with their effectiveness in producing nAChR desensitization.…”
mentioning
confidence: 99%
“…It is possible that nicotine metabolites produced by CYP2A5 enhance alcoholic fatty liver. On the other hand, metabolites of nicotine have a very low potency to bind to nAChRs (Vainio and Tuominen, 2001). Thus the cell-cell or organ-organ interaction as postulated above would be impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine exerts its cellular functions in neuronal cells through nicotinic acetylcholine receptors (nAChRs) (Itier and Bertrand, 2001). Cotinine, a metabolite of nicotine, has much lower potency to bind to nAChR (Vainio and Tuominen, 2001). CYP2A6 is a major enzyme which metabolically inactivates nicotine in humans, while in mice the enzyme which inactivates nicotine is CYP2A5, a mouse ortholog of human CYP2A6 (Su and Ding, 2004).…”
Section: Introductionmentioning
confidence: 99%